Hubungan Pengetahuan Tentang Manajemen Bencana Dengan Prevention Masyarakat Dalam Menghadapi Bencana Gunung Meletus Pada Kepala Keluarga Di Rt 06/Rw 01 Dusun Puncu Desa Puncu Kecamatan Puncu-Kediri - Didit Damayanti; Pria Wahyu R.G; Muhanni’ah Muhanni’ah (coba, 2017)
Introduction: Disaster management is a dynamic, continual, and integrated process as to increase the qualities of the actions which are relevant to the process of observation and analysis of disaster as well as minimalizing the negative impacts, mitigation, readiness, early warning, immediate emergency, rehabilitation and reconstruction. The aim of this research is to analyse theconnection between disaster management and the prevention of community breakdown in order to face a volcanic eruption for every head of household. Method: The design of this research is correlational research with a cross sectional approach. The demographic group that is used for this research is the head of households in Rt 06/Rw 01 dusun Puncu desa Puncu, by using the purposive sampling technique which has been collected from the sampling of the 33 heads of households. Independent variable is the knowledge of disaster management, and the dependent variable is the prevention of community breakdown in the handling of the disaster. The data has been received by using the questionnaire, and the results have been analysed by using spearman rho test. Result: As according to the statistics test, it is found that p-value= 0,000 on the significant level (α) = 0,05 and r = 0,752. It is concluded that there is a connection between knowledge and the prevention of community breakdown in handling of the volcanic eruption in Rt 06/Rw 01. This research shows that the level of knowledge within the community about disaster management and prevention in handling volcanic eruption has been increasing. Conclution: This is shown by the capability of the community in mitigating the effects of the disaster. It is hoped that the community will further engage in training education and simulation to reduce the negative impacts of a disaster. The location where the participants resideis Kelud Volcano, and it is therefore hoped that the communities are willing to participate in better handling of any disaster by joining the education training and simulation Kata kunci : Pengetahuan, Manajemen bencana, Prevention.